Studi Literatur Perancangan Arsitektur Data dan Aplikasi pada Perusahaan Telekomunikasi - Jason, Jason; Sutanto, Jefferson; Angkasa, Verrel; Darmana, Vicky; Maulana, Ade (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Enterprise Architecture (EA) serves as a blueprint for aligning business processes and IT systems to achieve organizational objectives. It provides a structured framework for integrating and optimizing various business units, enhancing overall effectiveness and maximizing outcomes. A well-defined EA is crucial for achieving business success. This research delves into the analysis of data and application modeling approaches in EA frameworks. Telecommunication companies, like other organizations, rely on EA to integrate and align their business processes and data with their corporate mission. Employing a qualitative literature review methodology, this study aims to identify the most prevalent data and application modeling approaches in EA frameworks, providing valuable insights for telecommunication companies seeking to refine their EA models in the future.